Management of The Implementation of The National Curriculum Based on Islamic Boarding School Education To Improve The Quality of Madrasah Aliyah (Descriptive Analytical Study at MA Al-Masthuriyah, MA Sunanul Huda, MA Al-Amin, Sukabumi Regency) - Irman Irman; Iim Wasliman; Waska Warta; Sayid Muhammad Rifky Naufal (UNIVERSITAS PAKUAN, 2023)
One of the efforts to improve the quality of education is the application of a curriculum that is in accordance with the needs and developments of the times. Reality shows that the practice of national education with a curriculum that is made and structured in such a way has even been refined many times, has not been able to present an Indonesian human figure with a complete personality.Efforts to achieve the quality of education as expected by all components of the nation have been carried out, including by issuing various policies that support both from an institutional perspective, human resources and the operationalization of quality implementation in schools and madrasas, including Law no. 20 of 2003 concerning the National Education System, Law no. 14 of 2005 concerning Teachers and Lecturers and PP No. 19 of 2005 concerning National Education Standards, and most recently the Minister of Education and Culture of the Republic of Indonesia Number 28 of 2016 which states that Education Quality Assurance is a systematic, integrated and sustainable mechanism to ensure that the entire process the implementation of education is in accordance with quality standards. Islamic boarding school-based schools such as MA Al-Masthuriyah, MA Sunanul Huda and MA Al-Amin in Sukabumi Regency implement education by combining general education and religious education into one curriculum building. With this approach, all formal school subjects and activities cannot be separated from the frame of teachings and messages of Islamic values. There is no dichotomy, separation, and secularization where lessons and all discussions are separated from Islamic values and teachings, or